Sacituzumab govitecan as a therapeutic breakthrough in the treatment of triple-negative breast cancer: a systematic review of clinical trials - Piekarz, Julia; Picheta, Natalia; Pobideł, Jakub; Szklener, Katarzyna; Skórzewska, Magdalena (Frontiers in Immunology, 2026)
BackgroundTriple-negative breast cancer (TNBC) is one of the most aggressive types of breast cancer (BC), most commonly diagnosed in young premenopausal women. It is characterized by the absence of estrogen receptor (ER), progesterone receptor (PR) and human epidermal growth factor receptor 2 (HER2). For this reason, therapeutic options using hormone therapy or targeted anti-HER2 treatment are significantly limited. TNBC is associated with a poor prognosis, which requires the search for new treatment strategies. A promising option is the use of an antibody-drug conjugate (ADC) directed against Trophoblast cell-surface antigen 2 (Trop-2), namely Sacituzumab govitecan (SG). Recent findings indicate that, beyond its direct cytotoxic effect, SG may also induce immunogenic cell death, remodel the tumor immune microenvironment, and enhance antitumor immune responses—features that make it a molecule of particular relevance in immuno-oncology.Materials and methodsA systematic review was conducted based on databases from PubMed, Web of Science and the ClinicalTrials.gov registry using the keywords: ‘Sacituzumab govitecan’, ‘Triple-negative breast cancer’, ‘Antibody–drug conjugate’, ‘metastatic triple-negative breast cancer’, ‘Trop-2’. The inclusion criteria covered studies from 2017 to 2025. Ultimately, after a thorough analysis, 4 randomized controlled trials (RCTs) and 4 single-arm studies were included in the review.ResultsAnalysis of clinical trial results evaluating the safety and efficacy of SG in TNBC therapy showed promising therapeutic potential for the drug. Significant improvements were observed in key clinical parameters, such as overall response rate (ORR) and progression-free survival (PFS). In addition, the safety profile was acceptable and consistent with previous reports, with the most commonly reported adverse events being neutropenia, diarrhea and alopecia, which were well controlled in most cases.ConclusionDue to its aggressive course and poor prognosis, TNBC remains a therapeutic challenge. SG is a promising therapeutic option, but further studies are needed, especially randomized controlled trials and studies on combinations with immunotherapy, to improve treatment outcomes and quality of life for patients. Importantly, SG also exhibits immunomodulatory potential through the induction of immunogenic cell death and enhancement of immune effector activity, positioning it as a bridge between cytotoxic and immune-based therapeutic strategies in TNBC.